AKTA OTENTIK RAPAT UMUM PEMEGANG SAHAM (RUPS) MELALUI MEDIA TELEKONFERENSI (Mekanisme Pembuatan dan Kekuatan Pembuktiannya) - Rizkianti, Wardani (Jurnal Yuridis, 2017)
While the times and technology, the implementation of the GMS also undergone a transformation from conventional systems towards the use of electronic systems with the use of telecommunications technology. As stipulated in Article 77 of the Company Law which legitimacy implementation of the GMS teleconferencing and mandated obligation of making the minutes of the meeting . Viewed from one side , Article 77 of the Company Law provides legitimacy in making authentic deed AGM via media teleconference on the other hand there is disharmony with the related regulations , especially Law Notary No. 30 of 2004 ( UUJN ) and Law No. 2 of 2014 on Amendment Act No. 30 of 2004 concerning Notary ( UUJN - P) , giving rise to concerns regarding the exact mechanism and strength of evidence. This study is a first step in reforming the national legal framework in order to accommodate the dynamics of telematics technology in a deed in Indonesia .